2014
DOI: 10.1620/tjem.234.221
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality in Career Advancement for Females in Japanese Academic Surgery

Abstract: During the past three decades, the participation of women in medicine has increased from 10. 6% (1986) to 19.7% (2012) in Japan. However, women continue to be underrepresented in the top tiers of academic medicine. We highlight gender inequality and discuss the difficulties faced by female surgeons in Japanese academic surgery. Using anonymous and aggregate employment data of medical doctors at Kyoto University Hospital from 2009 and 2013, and a commercially-published faculty roster in 2012-2013, we compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…[610] Okoshi et al . (2014) noted that the number of women in medicine in Japan had increased from 10.6% in 1986 to 19.7% in 2012, but they were underrepresented regarding academic appointments, particularly in surgery [Table 2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[610] Okoshi et al . (2014) noted that the number of women in medicine in Japan had increased from 10.6% in 1986 to 19.7% in 2012, but they were underrepresented regarding academic appointments, particularly in surgery [Table 2].…”
Section: Resultsmentioning
confidence: 99%
“…(2014) noted that the number of women in medicine in Japan had increased from 10.6% in 1986 to 19.7% in 2012, but they were underrepresented regarding academic appointments, particularly in surgery [Table 2]. [6] Furthermore, a review of data from Kyoto University Hospital (KYU) (2009–2013), revealed there were no female associate or full professors in surgery. Wilkes et al .…”
Section: Resultsmentioning
confidence: 99%
“…A rising number of female medical students, approaching nearly gender parity, in the entering classes of US medical schools confirm this trend [11,27]. Also in other countries is the number of female medical students steadily rising [28]. But surprisingly, surgery, especially academic surgery, and it subspecialties are still dealing with a paucity of female applicants, demonstrated by poor numbers of female surgical trainees over the last decades [27,[29][30][31].…”
Section: Demands/requirementsmentioning
confidence: 99%
“…T he representation of women in the workplace has been the focus of discussion worldwide. [1][2][3][4] Japan is known for its devastatingly low female representation in employment by industries among the Organization for Economic Co-operation and Development (OECD) member nations. Further, Japan had the lowest female proportion of seats on the boards of the largest publicly listed companies in 2015 (i.e., only 3%).…”
mentioning
confidence: 99%